A conceptual study on contingent impact of external integration on innovation SME business success relationship - Khairuddin, Sheikh M. H. S.; Qureshi, Zuhaib Hassan; Wahid, R. A.; Tehseen, Shehnaz *; Pathan, Z. H.; Khan, M. R. K. (Sciedu Press, 2019)
It is widely acknowledged in the existing studies that innovation has the critical role in firms’ performances. Moreover, it has been acknowledged that innovative activities are the main sources of growth, survivability, and success for SMEs firms. In the setting of entrepreneurship, earlier studies have claimed that innovation is the integrated element of entrepreneurship. However, the existing studies have also revealed inconsistent findings regarding the impacts of innovation on firm’s performances under various contexts. Thus, this study claims that there should be a moderator to facilitate the relationship between innovations and firm’s performances. Therefore, this study has introduced the external integration as a moderator to improve the relationship between types of innovations and firm’s performances. The main objective of the study is to identify the relationship between various types of innovations including process innovation, product innovation, marketing innovation, and organizational innovations and business success operationalized with four dimensions including perceived financial performance, perceived non-financial performance, perceived business growth, and perceived performance relative to competitors) under the moderating role of external integration. Three theories namely Strategic Contingency Theory (SCT), Resource Dependence Theory (RDT), and Resource Based View (RBV) have been integrated to develop the proposed theoretical framework. The recent literature has been taken to gather the information about the variables that helped current study to develop a theoretical frame work and then eight propositions have been developed based on proposed theoretical framework. The external integration as a moderator between innovations and business success is the main theoretical contribution of this study. Furthermore, limitations have been stated at the end and recommendations have been made for future research.